Knock-down and speed of kill of a combination of fipronil and permethrin for the prevention of Ctenocephalides felis flea infestation in dogs. Issue 1 (December 2016) - Halos, Lénaïg; Fourie, Josephus; Fankhauser, Becky; Beugnet, Frederic
Abstract Background A topical combination of fipronil + permethrin (Frontline Tri-Act®/Frontect®, Merial) has recently been developed to control fleas, ticks, mosquitoes, sandflies and stable flies on dogs. Two studies were conducted to assess its speed of kill and knock-down effect onCtenocephalides felis fleas. The combination was compared to either fipronil alone or to a combination of permethrin, dinotefuran, and pyriproxyfen, Methods In each study, 18 dogs were randomly allocated to one of three groups: (Group 1: untreated dog; Group 2: treated once on D0 with the combination of fipronil and permethrin; Group 3: treated once on D0 either with fipronil alone (study 1) or with a combination of permethrin, dinetofuran and pyriproxyfen (study 2)). Each dog was infested with 100 unfed adultC. felis fleas on Days 2 (study 2), 7, 14, 21 and 28. Fleas were collected from dogs at 1 h and 12 h post- infestations (PI) (study 1) or at 2 h and 6 h PI (study 2) to assess efficacy and from collection pans underneath cages 1 h (study 1) or 5 min (study 2) PI to assess knock-down effect. Results All treated dogs had significantly (p ≤ 0.01) lower flea counts than untreated dogs at every time point in both studies. For a whole month, a significant knock-down effect against infesting fleas is obtained in five minutes PI with the combination of permethrin and fipronil. Complete efficacy (>95 %) was achieved in 1 h (study 1) or 2 h (study 2) PI for 14 days and by 6 h PI for all challenges conducted throughout the month. Efficacy remains >85 % at 2 h PI for the whole month. A significantly higher efficacy of the fipronil + permethrin combination compared to other treatments was demonstrated at the earliest time points for the month (1 h knock-down effect and insecticidal efficacy compared to fipronil alone; 5 min knock-down effect compared to the combination of permethrin + dinetofuran + pyriproxyfen). Conclusions The rapid flea knock-down effect and speed of kill demonstrated by the spot on combination of fipronil + permethrin provide a reliable strategy against flea infestations in dogs.